Assessing the social and economic impact of improved banana varieties in East Africa - Lusty, Charlotte; Smale, Melinda (International Food Policy Research Institute, 2003)
Proceedings of an Interdisciplinary Research Design Workshop jointly organized by the International Network for the Improvement of Banana and Plantain (INIBAP) and the International Food Policy Research Institute (IFPRI). Equatoria Hotel, Kampala, Uganda, November 7-11, 2002.